2019
DOI: 10.1115/1.4042643
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Axis Wind Turbine Aerodynamics: Summary and Review of Momentum Models

Abstract: Momentum models or streamtube models represent one of the fundamental approaches in modeling the aerodynamics of straight bladed vertical axis wind turbine (SB-VAWT) of Darrieus type. They are based on momentum (actuator disk) theory and widely used in performance evaluation of VAWTs. In this short review, the authors have strived to compile the basic momentum models that have been widely assumed in the literature for design and performance estimation of SB-VAWTs of Darrieus type. A comprehensive demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The general mathematical expressions at a specific location of the blade and the input parameters used for the aerodynamic simulation are described below [25,29,30].…”
Section: General Mathematical Expressions For Aerodynamic Analysis Of Sb-vawtmentioning
confidence: 99%
See 2 more Smart Citations
“…The general mathematical expressions at a specific location of the blade and the input parameters used for the aerodynamic simulation are described below [25,29,30].…”
Section: General Mathematical Expressions For Aerodynamic Analysis Of Sb-vawtmentioning
confidence: 99%
“…The advantages of this model can be seen through the fact that it is relatively simple to implement and gives better correlation between calculated and experimental results [25]. However, the major drawback of this model is to give over prediction of power for a high solidity turbine, and there appears to be a convergence problem for the same type of turbine, especially in the downstream side and at the higher tip speed ratio [29].…”
Section: Double Multiple Stream Tube Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The omnidirectional operations of vertical axis wind turbines allow harnessing winds that frequently vary their directions, without requiring additional orientation systems [1,2]. Likewise, recently it was shown that vertical axis wind turbines can operate at shorter distances between rotors than horizontal axis wind turbines, which allow a greater number of turbines to be arranged in the same site area [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the low carbon economy goal of 2050 needs constant progress of energy harvesting by renewable energy sources to attain 18% of the global electricity consumption [8]. The most commonly used wind turbines are horizontal axis wind turbines (HAWT) and vertical axis wind turbines (VAWT) [9,10]. Among these two wind turbines, VAWT shows better characteristics, particularly for cities and semi-urban areas [11].…”
Section: Introductionmentioning
confidence: 99%